Diversity of viruses and viroids infecting Taro in Kenya based on small RNA sequencing and pcr detection - Muruu, David; Kinyua, J.; Kepue, M.; Kerubo, L.; Njaci, I.; Mware, Bernard (AJPO JOURNALS, 2022)
Purpose: Viral diseases cause severe yield losses and quality decline in crops worldwide. Despite their economic significance, the occurrence and distribution of the major viruses and viroids infecting Taro in Kenya remain poor, limiting the development of robust disease management strategies to mitigate their spread. This study thus aimed to identify the viruses and viroids infecting Taro in Kenya as a basis for developing effective management strategies to support the prevention and control of Taro viruses. Methodology: Viral surveys and sampling were conducted across nine Taro-growing counties with diverse agroecological conditions in Kenya to determine the incidence and distribution of viruses affecting Taro. Leaf and whole plant samples of symptomatic edible and wild Taro were collected for PCR, RT-PCR, and small RNA sequencing assays to determine the diversity of viruses and viroids infecting Taro. Results: Disease-like symptoms, including stunting, leaf rolling, shrinkage, deformed leaves with mosaic and yellow veins, and dwarfism, were observed. An overall mean disease incidence of 32-60% was recorded in all sites surveyed. Small RNA sequencing revealed the presence of both DNA and RNA viruses. Detected DNA viruses included the Taro Bacilliform Virus (TaBV) and Taro Bacilliform CH Virus (TaBCHV), badnaviruses specific to Taro, the sweet potato Badnavirus B, sugarcane bacilliform virus, and sweet potato leaf curl virus. The RNA viruses included the sweet potato feathery mottle and Phaseolus vulgaris alphaendornavirus. A Citrus exocortis viroid was also detected. Interestingly, the wild relatives of Taro displayed very few viral sequence hits. This study reports the Taro viruses and viroids circulating in Kenya and is the first to describe the incidence, distribution, and sequence variability of TaBV in Kenya. Recommendations: Future studies should focus on developing effective management strategies to support the prevention and control of Taro viruses, including genetic resources for virus-Taro interactions, removing infected crops, controlling insect vectors, and developing virus-free planting materials.